Redescription of Ateleopus japonicus Bleeker 1853, a senior synonym of Ateleopus natalensis Regan 1921 (Teleostei: Ateleopodiformes: Ateleopodidae) - Kaga, Tatsuya (Zootaxa, 2017)
Ateleopus natalensis Regan 1921, described from off the coast of Natal, South Africa, has been regarded as a valid species. Regan (1921) stated that the difference between the two species is the condition of the lower-jaw teeth: toothless in A. natalensis vs. teeth present in Ateleopus japonicus Bleeker 1853. However, the condition of lower-jaw teeth of Ateleopus has been proved an unreliable character because the lower-jaw teeth are very deciduous. Although Regan (1921) also implied that the differences between the two species include several body proportions, my examination of two syntypes and non-type specimens of A. natalensis from the western Indian Ocean revealed their close similarity to the range of many specimens of A. japonicus. Ateleopus japonicus is redescribed as a senior synonym of A. natalensis.